2022
DOI: 10.3390/aerospace9070336
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Sintering of DLP Printed Alumina Ceramics

Abstract: Digital Light Processing (DLP) technology exhibits the capability of producing components with complex structures for a variety of technical applications. Postprocessing of additively printed ceramic components has been shown to be an important step in determining the final product resolution and mechanical qualities, particularly with regard to distortions and resultant density. The goal of this research is to study the sintering process parameters to create a nearly fully dense, defect-free, ceramic componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…According to the thermal degradation behavior of 3D printed embryo, the degreasing and sintering process was determined to complete the removal of organic matter and the densification of alumina particles 25–29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the thermal degradation behavior of 3D printed embryo, the degreasing and sintering process was determined to complete the removal of organic matter and the densification of alumina particles 25–29 …”
Section: Resultsmentioning
confidence: 99%
“…The curing behavior of various photoinitiators is shown in removal of organic matter and the densification of alumina particles. [25][26][27][28][29] In this study, the ceramic green body was subjected to thermogravimetric analysis (Figure 5A) and the temperature curve of the degreasing was determined (Figure 5B). It can be observed that…”
Section: Influences Of the Photoinitiator On The Slurrymentioning
confidence: 99%
“…where P is the applied load (N), and h is the notch depth (mm). To observe the surface morphology of the samples, a dual-beam focused ion beam scanning electron microscope (FIB-SEM) (GX4, Thermo Fisher, Waltham, MA, USA) was utilized to examine the microstructure of the sample surfaces [33]. Additionally, the FIB-SEM's integrated EDS system was employed to analyze the elemental distribution and composition of the materials.…”
Section: 17 X For Peer Review 9 Of 19mentioning
confidence: 99%
“…In addition, a sufficient sintering temperature is necessary, as the ceramic densification process is incompletely attained when an improper heating temperature is used in the sintering process, resulting in a degradation of the material's physical properties. Therefore, optimal sintering temperatures should be investigated appropriately in advance to fully exploit the potentialities of ceramic materials [30].…”
Section: Introductionmentioning
confidence: 99%